Highly-conducting molecular circuits based on antiaromaticity - Fujii, Shintaro; Marqués-González, Santiago; Shin, Ji-Young; Shinokubo, Hiroshi; Masuda, Takuya; Nishino, Tomoaki; Arasu, Narendra P; Vázquez, Héctor; Kiguchi, Manabu (Nature communications, 2017)
Aromaticity is a fundamental concept in chemistry. It is described by Hückel's rule that states that a cyclic planar π-system is aromatic when it shares 4n+2 π-electrons and antiaromatic when it possesses 4n π-electrons. Antiaromatic compounds are predicted to exhibit remarkable charge transport properties and high redox activities. However, it has so far only been possible to measure compounds with reduced aromaticity but not antiaromatic species due to their energetic instability. Here, we address these issues by investigating the single-molecule charge transport properties of a genuinely antiaromatic compound, showing that antiaromaticity results in an order of magnitude increase in conductance compared with the aromatic counterpart. Single-molecule current-voltage measurements and ab initio transport calculations reveal that this results from a reduced energy gap and a frontier molecular resonance closer to the Fermi level in the antiaromatic species. The conductance of the antiaromatic complex is further modulated electrochemically, demonstrating its potential as a high-conductance transistor.